THE EFFECT OF APPLICATION OF SCOR & HOR PHASE 1 & 2 METHODS IN ANALYZING RISK AND STRATEGY DESIGNING IN THE SUPPLY CHAIN PART OF PT. Unicharm Indonesia. - Sayuti, Muhamad; Z. Wathoni, Akda; Kaniawati, Keni (International Journal of Psychosocial Rehabilitation, 2020)
In supply chain activities there is always the potential for risk to arise, therefore risk management is very necessary for handling risks. PT. Unicharm Indonesia is a manufacturer of baby diapers, adult diapers, sanitary napkins and wet tissue no. in Indonesia it is no wonder that supply chain activities are so complex. And potentially full of risks. Therefore, it is necessary to do a risk analysis and design of mitigation actions, to mitigate risks or disturbances that have the potential to arise in the supply chain process of raw materials until the finished product is ready to sell to the market. This research was conducted using the house of risk model consisting of 2 phases and with the SCOR concept. The first phase is the identification of risks and risk agents, which then measure severity and occurrence levels and calculate aggregate risk priority (ARP) values. Whereas in the second phase, it is the spread of strategies to reduce the risks that occur. After doing the research there are 29 risk events and 45 risk agents which are then made a paretto diagram to see which risks need to be done in designing strategies to mitigate the risks that occur.